Continuous electrical pumping membrane process for seawater lithium mining - Li, Zhen; Li, Chunyang; Liu, Xiaowei; Cao, Li; Li, Peipei; Wei, Ruicong; Li, Xiang; Guo, Dong; Huang, Kuo-Wei; Lai, Zhiping (Energy & environmental science, 2021)
Seawater contains significantly larger quantities of lithium than is found on land, thereby providing an almost unlimited resource of lithium for meeting the rapid growth in demand for lithium batteries. However, lithium extraction from seawater is exceptionally challenging because of its low concentration (∼0.1-0.2 ppm) and an abundance of interfering ions. Herein, we creatively employed a solid-state electrolyte membrane, and design a continuous electrically-driven membrane process, which successfully enriches lithium from seawater samples of the Red Sea by 43 000 times ( i.e. , from 0.21 to 9013.43 ppm) with a nominal Li/Mg selectivity >45 million. Lithium phosphate with a purity of 99.94% was precipitated directly from the enriched solution, thereby meeting the purity requirements for application in the lithium battery industry. Furthermore, a preliminary economic analysis shows that the process can be made profitable when coupled with the Chlor-alkali industry. Lithium was enriched up to 10 000 ppm from seawater by a continuous electrical pumping membrane process and collected as battery-grade product by simple precipitation.